Abstraction, belonging and comfort in the prison classroom. Issue 3 (November 2022) - Little, Ross; Warr, Jason
Prison education, at the institutional and policy level, is too often about the use value of qualifications, rather than the exchange value inherent in the experience of learning. This article explores how abstract discussion can be used to resolve this problem by facilitating the production and exchange of pedagogical capital in a prison classroom. The development of pedagogical capital, a form of symbolic capital related to learning, enhanced the sense of belonging and comfort experienced by students. The classroom comprised learners from university and prison, participating in informal discussion emanating from abstract questions. Based on interviews with, and feedback and reflections from, students participating in an eight-week course located in a higher security Category B training prison in the midlands of England ('HMP Lifer'), we discuss how pedagogical capital was produced and maintained. Firstly, it supported teachers to create a trustworthy learning space to discuss abstracted concepts and challenge each other – at an appropriate construal distance – without the discussion becoming too emotionally charged or exposing potential vulnerabilities. Secondly, it enabled students to use their own historical knowledge and experiences (narratives), creating a more equitable contributory space and reducing the risk of judgement. Thirdly, these elements combined to facilitate an iterative process of dialogical investment and exchange. The findings strongly suggest that the pedagogical approach was crucially important in creating a safe, trustworthy, equitable learning space in which students felt sufficiently at ease to exchange their thoughts and ideas as part of group discussion. We conclude that this pedagogical approach has wider implications for enhancing student resources, and fostering a sense of belonging in other, non-penal contexts, including higher education institutions.